Human Placental Mesenchymal Stem Cells for the Treatment of ARDS in Rat - Zurab Kakabadze; Nicholas Kipshidze; Teona Paresishvili; Nodar Kipshidze; Zurab Vadachkoria; David Chakhunashvili (Stem Cells International)
The acute respiratory distress syndrome (ARDS) is one of the main causes of high mortality in patients with coronavirus (COVID-19). In recent years, due to the coronavirus pandemic, the number of patients with ARDS has increased significantly. Unfortunately, until now, there are no effective treatments for ARDS caused by COVID-19. Many drugs are either ineffective or have a low effect. Currently, there have been reports of efficient use of mesenchymal stem cells (MSCs) for the treatment of ARDS caused by COVID-19. We investigated the influence of freeze-dried human placenta-derived mesenchymal stem cells (HPMSCs) in ARDS rat model. All animals have received intratracheal injection of 6 mg/kg of lipopolysaccharide (LPS). The rats were randomly divided into five groups: I: LPS, II: LPS+dexamethasone, III: LPS+HPMSCs, IV: HPMSC, and V: saline. ARDS observation time was short-term and amounted to 168 hours. The study has shown that HPMSCs are able to migrate and attach to damaged lung tissue, contributing to the resolution of pathology, restoration of function, and tissue repair in the alveolar space. Studies have also shown that the administration of HPMSCs in animals with ARDS model significantly reduced the levels of key cytokines such as IL-1β, IL-6, and TNF-α. Freeze-dried placental stem cell is a very promising biomaterial for the treatment of ARDS. The human placenta can be easily obtained because it is considered as a medical waste. At the same time, a huge number of MSCs can be obtained from the placental tissue, and there is no ethical controversy around their use. The freeze-dried MSCs from human placental tissue can be stored sterile at room temperature for a long time before use.